2022
DOI: 10.7717/peerj.12778
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and structure of the microbial community in rhizosphere soil of Fritillaria ussuriensis at different health levels

Abstract: Fritillaria wilt is a kind of soil-borne disease that causes a large reduction in the yield of Fritillaria ussuriensis. The diversity and structure of the soil microbial community are important factors affecting the health of Fritillaria ussuriensis. The analysis of the microbial community in the diseased and healthy soils provided a theoretical basis for revealing the pathological mechanism and prevention of Fritillaria wilt disease. In the present study, we sequenced the soil microorganisms from healthy (H),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 94 publications
3
12
0
1
Order By: Relevance
“…In the current study, the bacterial taxonomic compositions of F. przewalskii from different sites exhibited significant differences. Proteobacteria, Acidobacteria, Bacteroidetes, and Actinobacteria phyla formed the dominant microbiota despite habitat fluctuation (Figure 5A), which is consistent with previous studies (Shi et al, 2011;Jiao et al, 2022). Cyanobacteria was only the dominant phylum at RG site.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the bacterial taxonomic compositions of F. przewalskii from different sites exhibited significant differences. Proteobacteria, Acidobacteria, Bacteroidetes, and Actinobacteria phyla formed the dominant microbiota despite habitat fluctuation (Figure 5A), which is consistent with previous studies (Shi et al, 2011;Jiao et al, 2022). Cyanobacteria was only the dominant phylum at RG site.…”
Section: Discussionsupporting
confidence: 91%
“…The habitat is extremely vulnerable to natural influences, and human activities including over-harvesting, which have now resulted in F. przewalskii being declared endangered (Chen et al, 2013;Jin et al, 2019). Numerous studies indicated that knowing more about rhizosphere microbiota patterns may enhance the effectiveness of measure designed to assist the adaptation of F. przewalskii to the environment, and resist stress (Mahoney et al, 2017;Jiao et al, 2022). In particular, rhizosphere microbes can improve tolerance of Fritillaria to common diseases, such as wilt and root rot diseases, which can reduce crop yields (Baayen et al, 2001;Song et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance and diversity of soil microbial community decreased in the field evaluation of root rot disease in Fritillaria ussuriensis , while the population of pathogens in the healthy soil sample was quite low, indicating that the microbial community structure affected the health of F. ussuriensis ( Song et al, 2016 ). The diversity and structure of the microbial community were closely related to the health level of F. ussuriensis , this can lay a foundation for the systematic study on the interaction between microbial genera in the pathological process of F. ussuriensis ( Jiao et al, 2022 ).…”
Section: Diversity Of Rhizosphere Microorganisms Associated With Medi...mentioning
confidence: 86%
“…Aplikasi pestisida yang tinggi oleh petani ditunjukkan oleh tingginya kadar residu insektisida khususnya chlorpyrifos pada umbi bawang merah yaitu sebesar 0.229 mg/kg atau melebihi batas maksimum yang bisa ditoleransi menurut ISO 1313 (Jamaluddin et al, 2015). Selain memiliki dampak negatif terhadap musuh alami hama dan tanaman (fitotoksik), insektisida juga dapat menurunkan kesuburan tanah (Supreeth et al, 2016) dan sangat berbahaya bagi kesehatan manusia bahkan dalam konsentrasi yang rendah (Arisaputri & Bali, 2016;Jiao et al, 2022;Srinivasulu & Ortiz, 2017).…”
Section: Pendahuluanunclassified